Rising tiger : a thriller - Thor, Brad (New York : Emily Bestler Books, Atria, 2022)
"An unprecedented, potentially nation-ending threat has materialized on the world stage. Fearful of the global consequences of engaging this enemy, administration after administration has passed the buck. The clock, however, has run out and doing nothing is no longer an option. It is time to unleash Scot Harvath. As America$1 (Bs top spy, Harvath has the unparalleled skills and experience necessary to handle any situation, but this assignment feels different. Thrust into a completely unfamiliar culture, with few he can trust, the danger begins mounting the moment he arrives. Amidst multiple competing forces and a host of deadly agendas, it becomes nearly impossible to tell predator from prey. With democracy itself hanging in the balance, Harvath will risk everything to untangle the explosive plot and bring every bad actor to justice."--publisher's website.s
Keywords: Harvath, Scot -- (Fictitious character) -- Fiction; Intelligence officers -- Fiction; Terrorism -- Prevention -- Fiction; Political fiction; Suspense fiction